Audience’s perception towards using performing arts in enhancing English skills - Effandy, Noor Hasbullah ‘Arif M.; Abdul Latif @ Bapoo, Lilisuriani (Kulliyyah of Languages & Management (KLM), IIUM, 2021)
This study aims to investigate the audience’s perception towards the use of performing arts as a platform in enhancing English conversational skills. There are many research done by past scholars that investigated the use of either theatre, drama or short films in students’ English language learning, but there is little to no research done that look into audience’s perception on using theatre and short film to enhance English conversational (speaking and listening) skills. This research used a quantitative approach to collect the data by distributing a questionnaire to 101 Kulliyyah of Languages and Management (KLM) students who had watched at least one English theatre and one English short film. The findings answered all four research questions that fit the objective of the paper, in which the paper found that the audience does perceive that the use of theatre and short film can enhance their English speaking and listening skills. This paper served to be beneficial to future researchers and educators by providing new information in the field of performing arts and language teaching. Apart from that, the paper can also be beneficial to the government in their planning to devise new academic syllabus to improve Malaysian teaching methods when it comes to language teaching